2022
DOI: 10.1002/aac2.12055
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and aging: A call to action

Abstract: Background The intersection of cancer and aging is an emerging public health challenge in developed countries because of the aging and expansion of the population. Aims We convened a panel of experts to share their insights on this topic at the inaugural University of Florida Health Cancer Center's (UFHCC's) Cancer and Aging Symposium, which was held virtually in February 2022. Methods We featured presentations from four leading scientists, whose research spans multiple disciplines including basic science, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Studies based on natural compounds, such as flavonoids, demonstrated that the hallmarks of cancer, such as apoptosis, autophagy, and senescence, could intercept the hallmarks of aging [54]. The novelty of the present paper resides in the observation that both senescence and autophagy can be induced by IR treatment, possibly due to common modulators shared by these two processes.…”
Section: Discussionmentioning
confidence: 87%
“…Studies based on natural compounds, such as flavonoids, demonstrated that the hallmarks of cancer, such as apoptosis, autophagy, and senescence, could intercept the hallmarks of aging [54]. The novelty of the present paper resides in the observation that both senescence and autophagy can be induced by IR treatment, possibly due to common modulators shared by these two processes.…”
Section: Discussionmentioning
confidence: 87%
“…With aging as an HNC survivor, there may be biological changes that impact treatment outcomes and QoL. [8,9] Unfortunately, it can be difficult to differentiate age-related effects from treatment-related effects. Consult your medical team with changes that seem unusual.…”
Section: Part II Quality-of Life (Qol) As a Survivormentioning
confidence: 99%
“…As life expectancy has increased, geriatric oncology is becoming more critical due to the ever-increasing number of older cancer patients, which has so far concentrated mainly on traditional therapy tolerance ( 1 3 ). The correlation between incidence of malignancy and aging has been well established, and age-related immunological deterioration has been acknowledged for even longer ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%